Uptake and incorporation of PCBs by eastern Mediterranean rabbitfish that consumed microplastics. (January 2020) - van der Hal, Noam; Yeruham, Erez; Shukis, Diana; Rilov, Gil; Astrahan, Peleg; Angel, Dror L.
Abstract: Two experiments were executed to assess the feasibility of Polychlorinated Biphenyls (PCBs) transfer to fish tissues via MPs as a vector. PCBs that occur in the marine environment were tested for their adsorption to four different MP types. PCB congeners showed the highest adsorption levels to Polypropylene homo-polymer. The uptake of PCBs through MP ingestion was tested in an outdoor mesocosm using the herbivorous rabbitfish, Siganus rivulatus in the eastern Mediterranean Sea. Polypropylene homo-polymer particles (0.3–5.0 mm) pre saturated with 11 PCB congeners, in two concentrations (500 ng/g and 5000 ng/g), were mixed with dough and offered to the fish. PCBs were identified after two weeks in fish muscle tissues, but not in the liver. These results suggest that ingestion of contaminated MP by rabbitfish might harm them in the long run, and perhaps even those who consume them on a regular basis, e.g. rabbitfish predators and humans. Highlights: 11 PCB congeners had highest adsorption onto polypropylene homo-polymer. Rabbitfish were offered PCB-laced microplastics to test PCB transfer to tissues. After two weeks exposure PCBs were found in rabbitfish muscle but not in the liver.